Technologijomis grindžiamas mokymas ir mokymasis organizacijoje Technology enhanced teaching and learning in an organization - Trepulė, Elena (Vytautas Magnus University, 2015)
Technology enhanced learning concept, curriculum characteristics and processes are revealed and described in the monograph from philosophical, methodological, and empirical point of view and in the context of international experience. Integration of technology enhanced learning in an organization is based on the conception that information communication technologies should be in harmony with learning and teaching process to enhance these processes. Research implemented in three types of organizations - education, business and community - is presented in the book. Research results are focused on the strengths, limitations, learning and teaching needs in organizations, as well as input of staff of these organizations towards successful integration of technology enhanced learning. Virtual learning environment preferences, the need for technology enhanced learning perceived by the staff and the use and benefit of integration process for individuals and for the organization are discussed.